PENGARUH PEMBERIAN BAKTERI Rhizobium SpTERHADAP PERTUMBUHAN DAN PEMBENTUKAN BINTIL AKAR Mucuna bracteataDENGAN BIJI DAN STEK - Mardiana Wahyuni; Elisa Putri Sebayang (Institut Teknologi Sawit Indonesia, 2018)
Mucuna bracteata is one of legume cover land that is currently much used by oil palm and rubber plantations. The benefits of Mucuna bracteata are rapid growth, high biomass yields, N fixation from the air, tolerant to the diseases and pest attacks is not well-liked by livestock because the leaves contain high levels of phenol . Activity fixation of Nitrogen from the air were marked by the formation of rhizobia. In some plantation crop Mucuna bracteata rhizobia form a slow, nodules, formed one year after planting. Based on this research required the addition of rhizobium bacteria in order to inokulan the formation of rhizobia can take place properly. The research was carried out in the area of nursery STIPAP. Research has been done from April – July 2017 with the parameter length swirl (cm), number of leaves (strands), total dry weight, root nodule rhizobia. Treatment of planting material (M) and Rhizobium no significant eﬀect on the length of tendrils. Treatment of planting material (M) had significant eﬀect on leaf number parameter, treatment of seed planting material(M0) 135,50; (M1) 30,75 (64% compared to M0), Rhizobium treatment had no significant eﬀect on leaf number. The treatment of planting material had significant eﬀect on the number of root nodule (M0) 135.50; (M1 ¬) 57 ie 42%. The eﬀect on the weight of root nodule 15.06 g (M0), 10.08 g (M1) with a percentage of 64%. N content of Mucuna bracteata leaf in all observations belong to high category with value N> 3,1%.